Acute effect of a combined warm-up and kinesio tape application for muscle flexibility among amateur badminton players - Mohd Aris, Iman Nurhakim; Mohamed, Muhamad Noor; Mazaulan, Mardiana (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the combined effects of Kinesio Taping (KT) and sport-specific dynamic warm-ups on muscle flexibility and range of motion (ROM) in amateur badminton players. While dynamic warm-ups are established for increasing muscle temperature and neuromuscular efficiency, the supplemental impact of KT—theoretically used to enhance proprioception and blood flow—remains under-researched in this context. By evaluating these interventions together, the research seeks to determine if their synergy optimizes pre-performance strategies, reduces injury risk, and enhances the agility required for the multidirectional demands of badminton.